DNA damage response and anti-apoptotic proteins predict radiosensitization efficacy of HDAC inhibitors SAHA and LBH589 in patient-derived glioblastoma cells. Issue 2 (28th January 2015) - Berghauser Pont, Lotte M.E.; Naipal, Kishan; Kloezeman, Jenneke J.; Venkatesan, Subramanian; van den Bent, Martin; van Gent, Dik C.; Dirven, Clemens M.F.; Kanaar, Roland; Lamfers, Martine L.M.; Leenstra, Sieger
Abstract: HDAC inhibitors have radiosensitizing effects in established cancer cell lines. This study was conducted to compare the efficacy of SAHA, LBH589, Valproic Acid (VPA), MS275 and Scriptaid in the patient-derived glioblastoma model. In more detail, SAHA and LBH589 were evaluated to determine predictors of response. Acetylated-histone-H3, γH2AX/53BP1, (p)Chek2/ATM, Bcl-2/Bcl-XL, p21 CIP1/WAF1 and caspase-3/7 were studied in relation to response. SAHA sensitized 50% of cultures, LBH589 45%, VPA and Scriptaid 40% and MS275 60%. Differences after treatment with SAHA/RTx or LBH589/RTx in a sensitive and resistant culture were increased acetylated-H3, caspase-3/7 and prolonged DNA damage repair γH2AX/53BP1 foci. pChek2 was found to be associated with both SAHA/RTx and LBH589/RTx response with a positive predictive value (PPV) of 90%. Bcl-XL had a PPV of 100% for LBH589/RTx response. Incubation with HDACi 24 and 48 hours pre-RTx resulted in the best efficacy of combination treatment. In conclusion a subset of patient-derived glioblastoma cultures were sensitive to HDACi/RTx. For SAHA and LBH589 responses were strongly associated with pChek2 and Bcl-XL, which warrant further clinical exploration. Additional information on responsiveness was obtained by DNA damage response markers and apoptosis related proteins.